MEURER, J.L., BONINI, A., MOTTA-ROTH, D. (Orgs.). Gêneros: teorias , métodos , debates . SÃO PAULO: PARÁBOLA, 2005, 296p. - Bessa, Décio (Cadernos de Linguagem e Sociedade, 2010)
MEURER, J.L., BONINI, A., MOTTA-ROTH, D. (Orgs.). Gêneros: teorias , métodos , debates . SÃO PAULO: PARÁBOLA, 2005, 296p.